On a generality of confirmation bias: Individual differences perspective - Teovanović, Predrag; Berthet, Vincent (23rd Psychology Days in Zadar: Book of Selected Proceedings, 2024)
Although confirmation bias is being described as the most prominent cognitive bias, it is still unclear if it should be conceptualized as a unitary construct, or rather as an umbrella term for the group of related but independent phenomena. In the present study, we collected nine measures of individual differences in susceptibility to confirmation bias in different aspects of cognitive processing by employing and modifying several experimental paradigms. Results showed an overall preference for confirming over disconfirming information, but indicated that some cognitive tasks need further improvements in order to obtain more reliable measures. Nevertheless, the appliance of confirmatory factor analytic framework for testing hierarchically structured constructs showed that confirmation biases in information search, the weighing of evidence and memory recall are relatively independent constructs. Correlations among them were fair but insufficient to indicate the presence of a reliable second-order confirmation bias factor. In sum, the observed pattern of correlations suggests that it is more plausible to conceptualize confirmation bias as a multifaceted construct.